2018
DOI: 10.1177/1541931218621334
|View full text |Cite
|
Sign up to set email alerts
|

How Immersion, Presence, Emotion, & Workload Differ in Virtual Reality and Traditional Game Mediums

Abstract: The gaming experience is a critical component in the development and evolution of games. This study aims to assess the differences between virtual reality and a more traditional gaming experience in levels of emotion, immersion, and presence. We know that virtual reality is changing the way that people play games, but the extent to which virtual reality creates a more immersive and more present environment is still largely debated. Most of us can feel a difference but where does it lie? Similarly, if we are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…The observed difference in the 1st session and the absence of a difference in the later sessions’ durations postulates that when users are familiarized with the VR technology, while the influence of their gaming experience on the session’s duration becomes insignificant. In support of this, a recent study showed that user gaming experience does not affect the perceived workload of the users in VR (Lum et al, 2018). Hence, the level of familiarization of the participants with the VR technology appears to affect substantially the duration of the VR session.…”
Section: Discussionmentioning
confidence: 79%
“…The observed difference in the 1st session and the absence of a difference in the later sessions’ durations postulates that when users are familiarized with the VR technology, while the influence of their gaming experience on the session’s duration becomes insignificant. In support of this, a recent study showed that user gaming experience does not affect the perceived workload of the users in VR (Lum et al, 2018). Hence, the level of familiarization of the participants with the VR technology appears to affect substantially the duration of the VR session.…”
Section: Discussionmentioning
confidence: 79%
“…Computer technology that is increasingly developing makes VR also developed in various fields, ranging from education, health, psychology, and rehabilitation. Principally, the level of immersion and presence in the VR and other technology media are different (Lum et al, 2018). The critical factor of VR is the deep level of immersion and presence in the virtual sphere.…”
Section: Results and Discussion Vr Technology As Media In Communicationmentioning
confidence: 99%
“…The nature of resembling the reality of VR is often associated with the future of technology in fictional movies and series, but VR is also often identified as a supplement to video games experience (Ludlow, 2015). The user engagement in VR signifies the difference in the level of immersion and presence in the traditional game and VR's game (Lum et al, 2018). A virtual sphere with a high immersion of engagement calls for the roles of the designer in designing the virtual world environment (Welty & Setiawan, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, presence has been defined as the subjective and psychological reaction to immersive environments (Fromberger et al, 2015). As already introduced in the previous section of the present article, some studies have systematically used the terminology "immersion" and "presence" as synonyms (e.g., Jennett et al, 2008;Amin et al, 2016;Papachristos et al, 2017;Lum et al, 2018). In the present review, the word "presence" will be preferred for the description of the psychological and subjective feeling of being in a VE.…”
Section: Terminological Clarificationsmentioning
confidence: 99%